Pre-contact lens and pre-corneal tear film kinetics. Issue 3 (June 2019) - Guillon, Michel; Theodoratos, Panagiotis; Patel, Kishan; Gupta, Ruchi; Patel, Trisha
Abstract: Purpose: Contact lenses (CL) insulate the corneal surface from the environment. It is possible that they influence the corneal sensory mechanism that contribute to spontaneous blinking. The study objective was to quantify the pre-CL and pre-corneal tear film kinetics (TFK) over blink period. Methods: The study population was 202 soft CL wearers, 133 non-lens wearers. TFK were quantified via post-hoc masked analysis of HD Tearscope videos. The parameters were: Non-Invasive Break Up Time (NIBUT), Exposed Area % at initial break (EA 1st Break) and at blink (EA Blink), Interblink period (IB), Protective Index (PI) and exposure speed of surface dehydration (ES mm2/s). The TFK of CL wearers were compared to non-lens wearers. The hypothesis was that pre-CL TFK was inferior to pre-corneal, specifically greater tear film anomalies presence at blink. Results: The pre-corneal NIBUT was longer than pre-CL NIBUT (9.1 vs. 5.1s, p < 0.001). The EA 1st Break was smaller for pre-corneal than pre-CL (0.003 vs. 0.43%, p < 0.001). The mean IB time was similar for pre-CL and pre-corneal (9.4 vs. 9.8s, p = 0.213). The EA Blink % was smaller for pre-corneal than pre-CL (0.03 vs. 6.66%, p < 0.001). The ES was faster for pre-CL than pre-corneal (0.339 vs. 0.004, p < 0.001). The PI was greater for pre-corneal than pre-CL (99.9 vs. 97.1%, p < 0.001). Conclusions: Pre-CL TFK were significantly inferior than pre-corneal, confirmed the hypothesis. The NIBUT was shorter. Once the initial break occurred, ES was faster, and EA was much greater for pre-CL than pre-corneal. The differences identified may be an aetiological component of CL discomfort and the relationship between TFK and discomfort in contact lens wearers should be investigated.